A biomechanical investigation of thoracolumbar burst fracture under vertical impact loads using finite element method. (August 2019) - Guo, Li-Xin; Li, Wu-Jie
Abstract: Background: A sudden vertical impact load on spine can cause spinal burst fracture, especially in the thoracolumbar junction region. This study aimed at investigating the mechanism of spinal burst fracture under different energy vertical impact loads, producing the failure risk region to understand burst fracture, reducing nervous system damage and guiding clinical treatment. Methods: A nonlinear finite element model of T12-L1 motion segment was created to analyze the response of the vertical impact load. A rigid ball was used to impact the segment vertically to simulate the vertical impact load in practice. There were three different mass balls to represent the different loads: low energy, intermediate energy and high energy (respectively 13 J, 30 J and 56 J). The results of impact force, vertical displacement, stress, intradiscal pressure and contact force were obtained during the process. Findings: At low energy condition, the rigid ball rebounded rapidly. At intermediate energy condition, fractures were initiated in vertebral foramen and left rear regions on the superior cortical bone near the superior endplate of L1. At high energy condition, burst fracture occurred and a part of L1 was isolated from the model. Interpretation: The fracture occurred on the L1 segment only at the intermediate energy and high energy. The strength of vertebral body under low and intermediate energy was enough to support the impact. The burst fracture pattern at high energy was also observed in clinical practice. The findings may explain the mechanism of burst fracture. Highlights: Simulating the impact test of drop tower Reproducing burst fracture under three weights Spinal finite element model was assigned with failure material. The burst fracture process including initiation, propagation and termination was obtained.